2017
DOI: 10.13075/ijomeh.1896.01045
|View full text |Cite
|
Sign up to set email alerts
|

Did legal regulations change the reporting frequency of sharp injuries of medical personnel? Study from 36 hospitals in Łódź province, Poland

Abstract: Objectives: The aim of the study has been to analyze the epidemiological data on sharp injuries among health care workers before and after the implementation of regulations related to the conduct of the register of sharp injuries. Material and Methods: We hypothesized that the introduction of legislation would change the existing low reportability of sharp injuries and reporting incidents would increase. In Poland the binding regulations, dating back to 2013, require the employer to keep a record of sharp inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
1
8
0
2
Order By: Relevance
“…In the study Martins et al 65% of employees of a selected hospital in Portugal reported having experienced at least one NSSI in the last 5 years [20]. Most of the events, similar to ours and other studies (Polish and international) [21,22,23,24,25] concerned nurses. It should be noted that nurses are the most numerous professional group among medical employees, they perform the most treatments and usually have direct contact with patients.…”
Section: Discussionsupporting
confidence: 80%
“…In the study Martins et al 65% of employees of a selected hospital in Portugal reported having experienced at least one NSSI in the last 5 years [20]. Most of the events, similar to ours and other studies (Polish and international) [21,22,23,24,25] concerned nurses. It should be noted that nurses are the most numerous professional group among medical employees, they perform the most treatments and usually have direct contact with patients.…”
Section: Discussionsupporting
confidence: 80%
“…In collecting data, the authors encountered a number of limitations which are described in detail in the paper by Garus-Pakowska et al, 2018 [23]. It is worth to remember that the collected data is merely approximate; we estimated 45.2% underreporting but it is not known how many people failed to report the fact of puncture.…”
Section: Discussionmentioning
confidence: 95%
“…There are no precise Polish data on a number of the occupational NSIs. Previous studies in Poland were based on registers of the selected, usually single hospital [22], sometimes based on registers of several hospitals in a selected region of Poland [23, 24]. A second type of research is a questionnaire survey done among various groups of the HCWs [25–27].…”
Section: Discussionmentioning
confidence: 99%
“…Although surveys assessing the risk of occupationally BBIs have been conducted among HCWs in the region, most papers have concentrated on the frequency and circumstances of occupational exposure to blood [17, 28–30]. To the best of our knowledge, there has been no recent multicenter survey, conducted in the Central Europe after the implementation of the Council Directive, which assessed the epidemiology of SIs and the use of SDs in the context of HBV seroprevalence and vaccination of HCWs.…”
Section: Introductionmentioning
confidence: 99%